Response of Drought-Tolerant Hybrids to Environmental Yield Potential - T. Newell; K. Roozeboom; I. A. Ciampitti; Eric Adee; G. Cramer; J. D. Holman; A. Schlegel (Kansas Agricultural Experiment Station Research Reports, 2016)
Due to increasing non-irrigated corn acres, decreasing availability of irrigation water in some areas of western Kansas, and increasing water restrictions, producers are looking for more efficient ways to use available water. Drought-tolerant (DT) hybrid technologies are marketed for their ability to produce more stable yields in stress-prone environments. The objective of this research was to understand how DT and non-DT corn hybrids respond to a wide range of environmental conditions in terms of soil water status change, canopy indicators of stress, dry matter partitioning, and grain yield. Two DT hybrids, and one non-DT hybrid were compared in 2014 and 2015 at five locations in rain-fed, limited-irrigation, or fully irrigated regimes making a total of 18 environments. Grain yield was measured at all 18 environments, and biomass production was estimated at 14 of the environments. Yields of all hybrids were comparable in most environments, but as environment yields increased beyond 200 bu/a, one of the DT hybrids lagged behind the other two hybrids. Although one of the DT hybrids had slightly greater harvest index values than the other two hybrids in environments that resulted in a greater portion of dry matter allocated to grain, the differences were not consistent enough to be conclusive.
Keywords: DT corn hybrids; soil water; yield